$\dfrac{a}{b} = \dfrac{2b - 3c}{a} = \dfrac{4c - b}{c}$
Theo tính chất của dãy tỷ số bằng nhau, ta có:
$\dfrac{a}{b} = \dfrac{2b - 3c}{a} = \dfrac{4c - b}{c} = \dfrac{a+2b-3c+4c-b}{a+b+c} = \dfrac{a+(2b-b)+(4c-3c)}{a+b+c} = \dfrac{a+b+c}{a+b+c} = 1$
Do đó $\dfrac{a}{b} = 1 \Rightarrow a = b$
Thay $a = b$ vào $\dfrac{a}{b} = \dfrac{2b - 3c}{a}$, ta có
$\dfrac{a}{b} = \dfrac{2b - 3c}{a} \\
\Rightarrow \dfrac{b}{b} = \dfrac{2b - 3c}{b} \\
\Rightarrow \dfrac{2b - 3c}{b} = 1 \\
\Rightarrow 2b-3c=b \Rightarrow b = 3c$
Vậy An nói sai